2013
DOI: 10.1089/jpm.2013.0080
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Pain and Pain Treatment in a Western Kenya Referral Hospital

Abstract: Background: Pain is often inadequately evaluated and treated in sub-Saharan Africa (SSA). Objective: We sought to assess pain levels and pain treatment in 400 hospitalized patients at a national referral hospital in western Kenya, and to identify factors associated with pain and pain treatment. Design: Using face-validated Kiswahili versions of two single-item pain assessment tools, the Numerical Rating Scale (NRS) and the Faces Pain Scale-Revised (FPS-R), we determined patients' pain levels. Additional data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 38 publications
2
22
1
Order By: Relevance
“…Pain prevalence was high and among the most burdensome physical symptoms in our study. Several studies in HIV (Huang et al, 2013, Kolawole Wasiu and Alakija Kazeem, 2011, Richardson et al, 2009, Kimball and McCormick, 1996, Wakeham et al, 2017 and cancer (Huang et al, 2013) population have reported high prevalence of pain alongside ART. Several authors have reported that pain and other physical and psychological symptoms persist in HIV alongside ART (Harding et al, 2010, Lowther et al, 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Pain prevalence was high and among the most burdensome physical symptoms in our study. Several studies in HIV (Huang et al, 2013, Kolawole Wasiu and Alakija Kazeem, 2011, Richardson et al, 2009, Kimball and McCormick, 1996, Wakeham et al, 2017 and cancer (Huang et al, 2013) population have reported high prevalence of pain alongside ART. Several authors have reported that pain and other physical and psychological symptoms persist in HIV alongside ART (Harding et al, 2010, Lowther et al, 2014.…”
Section: Discussionmentioning
confidence: 99%
“…The NRS was found to be more responsive than a six-point VRS [ 17 ]; the most feasible and discriminative self-report scale as compared to a VAS or 5-point VRS [ 18 ]; and more sensitive and discriminative than a binary scale [ 19 ]. One study that compared an NRS to a Faces scale (a type of graphical scale that uses photographs or pictures showing a continuum of facial expressions) found both scales to be equally well understood [ 20 ], although a population of Swahili-speaking patients preferred the Faces scale over the NRS [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest variable interpretation of scores on an NRS. Chien et al 2013 [ 17 ] Instrument development and/or validation study, Direct, A The NRS is potentially more sensitive to clinical changes in comparison to the VRS Huang et al 2013 [ 20 ] Prospective study, Direct, A The Faces scale and the NRS were easily understood and well accepted by participants and should be implemented for daily use in the inpatient setting in order to gauge patients’ pain and response to pain treatment. Rothaug et al 2013 [ 19 ] Prospective study, Direct, A Binary answer format was proven to be a practical alternative to the NRS format for a screening instrument, however may not be as sensitive to discriminate levels of pain intensity as compared to the NRS.…”
Section: Resultsmentioning
confidence: 99%
“…A study of the prevalence and clinical correlates of pain conducted at the MTRH from March to July 2011 noted that 66% of inpatients had undertreated pain, with the highest pain scores noted in older adults as well as patients with HIV and cancer. 13 The palliative care team initiated a series of educational programs to increase the clinical competency of MTRH personnel regarding the principles of palliative care. The first training was offered in 2011 with 29 individuals participating in a 5-day training session.…”
Section: Resultsmentioning
confidence: 99%